Government procurement in Ecuador: analysis and perspective - Faz Cevallos, Wilson Eduardo; Fuentes Gavilanez, Lenin Estalin; Hidalgo Mayorga, Mariela; Guerrero Arrieta, Katherine Geovanna (Universidad Ciencia y Tecnología, 2023)
The purpose of this research was to analyze the situation of public procurement in Ecuador, considering both the previous political regime and the significant changes that have occurred with the implementation of the new public procurement law, as well as the principles that must be met. A methodology based on review and documentary analysis was used, considering current laws and current regulations. The results show that the need for annual planning and budget allocation is a crucial problem that must be solved in the country’s public procurement field. It is concluded that it is necessary to implement the new procedures established by the Organic Law of the National Public Procurement System to create a transparent, efficient, and dynamic contracting system that broadly benefits the nation and its inhabitants.